Dexmeditomidine as an Adjunct to Ropivacaine for Transversus Abdominis Plane (TAP) Block for Subumblical Surgeries - Ozair Noor Trumboo, Tantry Tariq Gani,; Reyaz Ahmed Qadri, Shahid Ahmad Mir,; Mohamad Akbar Shah, Khalid Sofi, (International Journal of Innovative Research in Medical Science, 2017)
Background and Aims: This prospective, randomized, double-blind study was done to evaluate the effect of addition of dexmedetomidine as an adjunct to ropivacaine in TAP (Transversus Abdominis Plane) block for lower abdominal/subumblical surgeries. Materials and Methods: Hundred ASA (American Society of Anesthesiologists) class I and II patients undergoing lower abdominal surgeries were enrolled to receive either ropivacaine alone (Group 1) or ropivacaine with dexmeditomidine (Group 2) in TAP block for postoperative analgesia at the end of surgical procedure performed under spinal anesthesia. Duration of analgesia, total amount of rescue analgesia, hemodynamic parameters, and any adverse events were monitored. Results: Analgesia in the postoperative period was better in Group 2 with comparable side effects. Conclusion: Hence, addition of dexemedetomidine to ropivacine in TAP lock significantly increases the duration of analgesia without increasing the side effects.